2005
DOI: 10.4049/jimmunol.174.2.1091
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipids Inhibit Lipopolysaccharide (LPS)-Induced Cell Activation: A Role for LPS-Binding Protein

Abstract: The inhibition of LPS-induced cell activation by specific antagonists is a long-known phenomenon; however, the underlying mechanisms are still poorly understood. It is commonly accepted that the membrane-bound receptors mCD14 and TLR4 are involved in the activation of mononuclear cells by LPS and that activation may be enhanced by soluble LPS-binding protein (LBP). Hexaacylated Escherichia coli lipid A has the highest cytokine-inducing capacity, whereas lipid A with four fatty acids (precursor IVa, synthetic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
68
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(73 citation statements)
references
References 39 publications
4
68
1
Order By: Relevance
“…These results could be explained by the formation of LTA⅐LBP complexes leading to inactivation of LTA and LBP functions. A similar mechanism has been suggested for the neutralization of sLBP by phospholipids (39). Interaction of LTA with serum proteins has been reported previously, but the data published on the requirement of soluble LBP are conflicting.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…These results could be explained by the formation of LTA⅐LBP complexes leading to inactivation of LTA and LBP functions. A similar mechanism has been suggested for the neutralization of sLBP by phospholipids (39). Interaction of LTA with serum proteins has been reported previously, but the data published on the requirement of soluble LBP are conflicting.…”
Section: Discussionmentioning
confidence: 78%
“…Cytokine Determination-Human TNF␣ and human IL-6 were determined in pooled cell-free supernatants of stimulated cells by sandwich enzyme-linked immunosorbent assay using monoclonal mouse antibody against human IL-6 and PODconjugated rabbit anti-human IL-6 antibody and monoclonal mouse antibody against human TNF␣ and POD-conjugated rabbit anti-human TNF␣ antibody, respectively (Intex, Muttant, Switzerland) as stated in detail elsewhere (39). Rat TNF␣ and human IL-8 were determined in pooled cell-free supernatants of stimulated cells by sandwich enzyme-linked immunosorbent assay using Cytosets from BIOSOURCE (Solingen, Germany) exactly according to the manufacturer's protocol.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have provided evidence that the antagonism of LPS activation through LBP/CD14/MD2/TLR4 is dependent upon the molecular class and species of phospholipid used as an antagonist (17)(18)(19)(20). We examined the molecular specificity of the POPG effect on RSV-elicited cytokine production by comparing the effects of POPG with a phospholipid counterpart containing a choline polar moiety, palmitoyl-oleoylphosphatidylcholine (POPC).…”
Section: Popg Specifically Attenuates Proinflammatory Cytokine Producmentioning
confidence: 99%
“…Additional studies have identified phosphatidylglycerol (PG) as an antagonist of LPS binding protein (LBP), and CD14 (18)(19)(20). Although PG constitutes about 10% of surfactant phospholipids, the high concentration of lipid in the extracellular surfactant layer within the alveolus, results in PG levels as high as 3.5 mg/mL This extraordinary level of PG is not found in any other tissue or mucosal surface in mammals.…”
mentioning
confidence: 99%
“…TNF-␣ was determined in pooled cell-free supernatants of stimulated cells by sandwich ELISA using monoclonal mouse Ab against human TNF-␣ and HRP-conjugated rabbit anti-human TNF-␣ Ab (Intex) as stated in detail elsewhere (37). IL-8 was determined in pooled cell-free supernatants of stimulated cells by sandwich ELISA using IL-8 cytoset from Biosource exactly according to the manufacturers' protocol.…”
Section: Cytokine Determinationmentioning
confidence: 99%